Method for producing inorganic sintered body

A resin composition with polyvinyl acetal and acetylated polyol is used to promote binder removal in a reducing atmosphere, addressing residual carbon and oxidation issues in inorganic sintered bodies, enhancing the reliability of electronic components.

CN119233956APending Publication Date: 2024-12-31SEKISUI CHEMICAL CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202380040603.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-12-13
Filing Date
2023-12-04
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

Existing methods for producing inorganic sintered bodies face challenges with residual carbon after sintering due to incomplete binder decomposition and oxidation of inorganic particles, particularly when using polyvinyl acetal resin, and the use of sintering aids like oxides of boron, silicon, and magnesium do not fully address reliability issues.

Method used

A method involving a resin composition containing polyvinyl acetal resin and acetylated polyol, with specific oxygen atom content and boiling point, is used to promote binder removal in a reducing atmosphere, reducing residual carbon and enhancing the reliability of electronic components.

Benefits of technology

The method effectively reduces residual carbon and inhibits oxidation of inorganic particles, resulting in high-reliability electronic components without increasing oxygen partial pressure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005134883140000241
    Figure BDA0005134883140000241
  • Figure BDA0005134883140000251
    Figure BDA0005134883140000251
Patent Text Reader

Abstract

Provided is a method for producing an inorganic sintered body with which it is possible to obtain a highly reliable electronic component by reducing residual carbon after firing. The present invention is a method for producing an inorganic sintered body, the method comprising: a resin composition production step for producing a resin composition containing a polyvinyl acetal resin, an acetic acid polyol, and inorganic particles; and a firing step for obtaining an inorganic sintered body by heating the resin composition to the sintering temperature of the inorganic particles, the acetic acid polyol having an oxygen atom content of 40 wt% or more. The content of the acetolated polyol in the resin composition is 5-40 parts by weight (inclusive) per 100 parts by weight of the polyvinyl acetal resin.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for manufacturing an inorganic sintered body. Background Art

[0002] In recent years, compositions in which inorganic particles such as ceramic powder and glass particles are dispersed in a binder resin have been used in the production of laminated electronic components such as ceramic capacitors.

[0003] Such ceramic capacitors are generally manufactured using the following method.

[0004] First, after adding additives such as a plasticizer and a dispersant to a solution prepared by dissolving a binder resin in an organic solvent, a ceramic raw material powder is added and uniformly mixed using a ball mill or the like to obtain an inorganic particle dispersed composition.

[0005] The obtained inorganic particle dispersion composition is cast on a release-treated support surface such as a polyethylene terephthalate film or a SUS plate using a doctor blade or a reverse roll coater, and after volatile components such as an organic solvent are distilled off, it is peeled from the support to obtain a ceramic green sheet.

[0006] Next, a conductive paste to be the internal electrode is applied to the obtained ceramic green sheets by screen printing or the like, and a plurality of these are stacked, heated, and pressure-bonded to obtain a laminate.

[0007] The obtained laminated body is heated to perform a process of removing components such as a binder resin by thermal decomposition, a so-called degreasing process, and then fired to obtain a ceramic sintered body having internal electrodes.

[0008] Furthermore, external electrodes are applied to the end surfaces of the obtained ceramic sintered body and fired, thereby completing a multilayer ceramic capacitor.

[0009] With the miniaturization of multilayer ceramic capacitors, polyvinyl acetal resin has been used as a binder resin in such inorganic particle dispersion compositions in recent years. In the manufacture of multilayer ceramic capacitors, sintering is performed in an inactive atmosphere to prevent oxidation of inorganic particles, but there is a problem that the sintering residue of the binder has an adverse effect on the reliability of the product.

[0010] In contrast, for example, Patent Document 1 discloses a method in which the debindering process before sintering a laminated ceramic body is divided into two stages: from 20°C to 400°C in an atmosphere with an oxygen concentration of less than 1%, and from 400°C to 600°C in an atmosphere with an oxygen concentration of more than 1%.

[0011] Patent Document 2 discloses a structure in which oxides of boron, silicon, magnesium, and lithium are used as a sintering aid for dielectric ceramics, thereby improving the reliability of the dielectric layer.

[0012] Prior art literature

[0013] Patent Literature

[0014] Patent Document 1: Japanese Patent Application Laid-Open No. 8-73273

[0015] Patent Document 2: Japanese Patent Application Publication No. 2005-104775 Summary of the invention

[0016] Problems to be solved by the invention

[0017] For polyvinyl acetal resin, when fired in an inert gas atmosphere, it starts to decompose around 300°C, undergoes decarboxylation and dehydration reactions, and stops losing weight at 450°C. At this stage, the structure of the resin has changed to soot (Japanese: coal), and it will not decompose without oxygen from the outside, so oxygen is introduced into the supply gas to promote the decomposition of the soot. However, even if oxygen is introduced from the outside as in Patent Document 1, it is difficult to supply oxygen to the inside of the ceramic, and the decomposition is not fully carried out.

[0018] In addition, when a sintering aid is used as in Patent Document 2, there are problems such as the need to add a large amount, difficulty in maintaining dielectric properties, and inability to be applied to various uses such as all-solid-state batteries.

[0019] An object of the present invention is to provide a method for producing an inorganic sintered body capable of reducing residual carbon after sintering and obtaining an electronic component with high reliability.

[0020] Means for solving problems

[0021] The present invention (1) relates to a method for producing an inorganic sintered body, which comprises: a resin composition preparation step for preparing a resin composition containing a polyvinyl acetal resin, an acetylated polyol and inorganic particles; and a sintering step for heating the resin composition to a sintering temperature of the inorganic particles to obtain an inorganic sintered body, wherein the oxygen atom content of the acetylated polyol is greater than 40 wt %, and the content of the acetylated polyol in the resin composition is greater than 5 wt % and less than 40 wt % relative to 100 wt % of the polyvinyl acetal resin.

[0022] The present invention (2) relates to the method for producing an inorganic sintered body according to the present invention (1), wherein the acetylated polyol is an acetylated product of at least one polyol selected from the group consisting of glycerol, pentaerythritol, diethylene glycol and triethylene glycol.

[0023] The present invention (3) relates to a method for producing an inorganic sintered body of the present invention (1) or (2), which further comprises, before the above-mentioned sintering step, a debindering treatment step of maintaining the temperature at a temperature of 250°C to 350°C in a nitrogen atmosphere for 1 hour to 5 hours.

[0024] The present invention (4) relates to a method for producing an inorganic sintered body according to any combination of any of the present inventions (1) to (3), wherein the sintering step is carried out at an oxygen partial pressure of 10 -10 It is carried out in a reducing atmosphere containing H2-N2-H2O gas at a pressure of less than MPa.

[0025] Hereinafter, the present invention will be described in detail.

[0026] The present inventors have conducted intensive research and have found that by adopting a method for producing an inorganic sintered body by preparing a composition containing a polyvinyl acetal resin and an acetic acid polyol having a specific structure and subjecting the composition to a heat treatment, it is possible to promote a debindering process and reduce residual carbon without increasing the oxygen partial pressure, inhibit oxidation of inorganic particles constituting an electrode layer, inhibit voids in a dielectric layer, and produce electronic components with high reliability, thereby completing the present invention.

[0027] The method for producing the inorganic sintered body comprises a resin composition production step of producing a resin composition containing a polyvinyl acetal resin, an acetated polyol, and inorganic particles.

[0028] By providing the resin composition preparation step, the binder removal process can be promoted without increasing the oxygen partial pressure in the firing step, thereby reducing residual carbon.

[0029] The resin composition preparation step preferably includes: a slurry composition preparation step of preparing a slurry composition containing a polyvinyl acetal resin, an acetated polyol, inorganic particles and an organic solvent; and a coating and drying step of coating the slurry composition on a substrate and drying it to prepare a resin composition.

[0030] The slurry composition contains a polyvinyl acetal resin.

[0031] The polyvinyl acetal resin described above functions as a binder.

[0032] The degree of polymerization of the polyvinyl acetal resin is preferably 200 or more and 4000 or less, more preferably 500 or more and more preferably 3000 or less, from the viewpoint of the coating film strength and sinterability of the slurry composition.

[0033] The degree of polymerization of the polyvinyl acetal resin refers to the degree of polymerization of the raw polyvinyl alcohol resin. The degree of polymerization of the raw polyvinyl alcohol resin can be measured by a method according to JIS K6726. In addition, when the polyvinyl acetal resin is a mixture of two or more, the degree of polymerization can be obtained by adding the values ​​obtained by multiplying the degrees of polymerization of each polyvinyl acetal resin by the proportion of the mixture.

[0034] The acetal group content of the polyvinyl acetal resin is preferably 50 mol% or more from the viewpoint of compatibility with the acetated polyol and sinterability, and is preferably 80 mol% or less from the viewpoint of preventing sheet erosion when the conductive paste composition is applied to the dielectric layer. The acetal group content is more preferably 60 mol% or more, and more preferably 75 mol% or less. The acetal group content is preferably 50 to 80 mol%, and more preferably 60 to 75 mol%.

[0035] The acetal group amount can be measured by, for example, NMR.

[0036] From the viewpoint of compatibility with acetated polyol and inhibition of sheet corrosion, the hydroxyl content of the polyvinyl acetal resin is preferably 16 mol% or more, preferably 50 mol% or less, more preferably 20 mol% or more, more preferably 33 mol% or less. The hydroxyl content is preferably 16 to 50 mol%, more preferably 20 to 33 mol%.

[0037] The amount of hydroxyl groups can be measured by, for example, NMR.

[0038] The acetyl group content of the polyvinyl acetal resin is preferably 0.1 mol% or more, preferably 20 mol% or less, more preferably 1 mol% or more, more preferably 15 mol% or less. The acetyl group content is preferably 0.1 to 20 mol%, more preferably 1 to 15 mol%.

[0039] The acetyl group amount can be measured by, for example, NMR.

[0040] The polyvinyl acetal resin preferably has an α-olefin unit in the main chain.

[0041] Since the hydrogen bonding force of the polyvinyl acetal resin is weakened by the α-olefin, the temporal stability of the viscosity can be improved or the screen printability can be improved.

[0042] Examples of the α-olefin include methylene, ethylene, propylene, isopropylene, butene, isobutylene, pentene, hexene, cyclohexene, cyclohexylethylene, and cyclohexylpropylene, and ethylene is particularly preferred.

[0043] The content of the α-olefin is preferably 1 to 20 mol%.

[0044] The content of the α-olefin unit in the polyvinyl acetal resin is preferably 1 mol% or more, preferably 20 mol% or less, more preferably 5 mol% or more, more preferably 15 mol% or less. The content of the α-olefin unit is preferably 1 to 20 mol%, more preferably 5 to 15 mol%.

[0045] By setting it as the said range, the solubility in an organic solvent can be fully improved.

[0046] The polyvinyl acetal resin may have other ethylenically unsaturated monomer units.

[0047] Examples of the other ethylenically unsaturated monomers include acrylic acid, methacrylic acid, fumaric acid (anhydride), maleic acid (anhydride), itaconic acid (anhydride), acrylonitrile, methacrylonitrile, acrylamide, methacrylamide, (3-acrylamide-3-dimethylpropyl)-trimethylammonium chloride, acrylamido-2-methylpropanesulfonic acid and its sodium salt, ethyl vinyl ether, butyl vinyl ether, N-vinyl pyrrolidone, vinyl chloride, vinyl bromide, vinyl fluoride, vinylidene chloride, vinylidene fluoride, tetrafluoroethylene, sodium vinyl sulfonate, and sodium allyl sulfonate.

[0048] From the viewpoint of dispersibility of inorganic particles, adhesion to substrates, and sinterability, the content of ethylenically unsaturated monomer units in the polyvinyl acetal resin is preferably 0.1 mol% or more and 10 mol% or less. The content of ethylenically unsaturated monomer units is preferably 0.1 to 10 mol%.

[0049] The polyvinyl acetal resin can be obtained, for example, by dissolving a polyvinyl alcohol resin in hot water, adding aldehyde in the presence of an acid catalyst so as to obtain a predetermined amount of acetal groups, allowing the mixture to react, and then washing with water, neutralizing, and drying.

[0050] The acid catalyst is not particularly limited, and both organic acids and inorganic acids can be used. Examples thereof include acetic acid, p-toluenesulfonic acid, nitric acid, sulfuric acid, and hydrochloric acid.

[0051] Examples of the base used for neutralization include sodium hydroxide, potassium hydroxide, ammonia, sodium acetate, sodium carbonate, sodium hydrogen carbonate, and potassium carbonate.

[0052] The polyvinyl alcohol resin is obtained by saponifying a vinyl ester polymer.

[0053] Examples of the vinyl ester include vinyl formate, vinyl acetate, vinyl propionate, and vinyl pivalate. From the perspective of economic efficiency, vinyl acetate is preferred.

[0054] In addition, the polyvinyl alcohol resin preferably contains an α-olefin in the main chain. The α-olefin weakens the hydrogen bonding force of the polyvinyl acetal resin, thereby improving the temporal stability of the viscosity or improving the screen printability.

[0055] The aldehyde used in the above reaction is not particularly limited, and examples thereof include formaldehyde (including paraformaldehyde), acetaldehyde (including paraldehyde), propionaldehyde, butyraldehyde, valeraldehyde, hexanal, heptaldehyde, 2-ethylhexanal, cyclohexylaldehyde, furfural, glyoxal, glutaraldehyde, benzaldehyde, 2-methylbenzaldehyde, 3-methylbenzaldehyde, 4-methylbenzaldehyde, p-hydroxybenzaldehyde (Japanese: p-hydroxybenzaldehyde), m-hydroxybenzaldehyde (Japanese: m-hydroxybenzaldehyde), phenylacetaldehyde, phenylpropionaldehyde, etc. These aldehydes may be used alone or in combination of two or more, and acetaldehyde and / or butyraldehyde are preferably used.

[0056] From the viewpoint of the coating strength and binder removability of the slurry composition, the content of the polyvinyl acetal resin in the slurry composition is preferably 2% by weight or more, preferably 8% by weight or less, more preferably 3% by weight or more, and more preferably 7% by weight or less. The content of the polyvinyl acetal resin in the slurry composition is preferably 2 to 8% by weight, more preferably 3 to 7% by weight.

[0057] The slurry composition may contain a binder resin other than the polyvinyl acetal resin.

[0058] Examples of other binder resins include acrylic resins, ethyl cellulose resins, other cellulose resins such as hydroxymethyl cellulose and carboxymethyl cellulose, polyester resins, epoxy resins, and polycarbonate resins.

[0059] The slurry composition contains acetated polyol.

[0060] The acetylated polyol is an acetylated product of a polyol, that is, an acetate ester, and may be a complete ester (Japanese: complete ester) or a partial ester (Japanese: partial ester).

[0061] The number of acetate units in the acetated polyol is preferably 2 or more and preferably 4 or less.

[0062] The acetic acid-modified polyol has a function as a binder removal aid.

[0063] The acetated polyol has an oxygen atom content of 40% by weight or more.

[0064] The acetated polyol has a large number of oxygen atoms in its molecule and burns by consuming its own oxygen even in a nitrogen atmosphere. When mixed with a binder resin such as the polyvinyl acetal resin, the pyrolysis of the binder resin is assisted. Therefore, the binder removal process can be promoted without increasing the oxygen partial pressure, and the sintering residue can be significantly reduced. In addition, the oxidation of inorganic particles can be suppressed, and ceramic products with high reliability can be produced.

[0065] The content of the oxygen atoms is preferably 41% by weight or more, more preferably 42% by weight or more. In addition, from the viewpoint of solubility in organic solvents, the content of the oxygen atoms is preferably 55% by weight or less, more preferably 50% by weight or less. The content of the oxygen atoms is preferably 40 to 55% by weight, more preferably 41 to 55% by weight, and further preferably 42 to 50% by weight.

[0066] The oxygen atom content is the content of oxygen atoms in one molecule, and can be calculated based on the molecular weight of the acetated polyol and the atomic weight of oxygen. Alternatively, the oxygen atom content can be calculated by setting the atomic weight of carbon to 12, the atomic weight of hydrogen to 1, and the atomic weight of oxygen to 16.

[0067] The acetated polyol preferably has a plurality of acetyl groups. The number of the acetyl groups is preferably 2 or more, and preferably less than 6.

[0068] The molecular weight per acetyl group is preferably 70 or more, and preferably 120 or less. When the molecular weight per acetyl group is 70 or more, the boiling point can be sufficiently increased, evaporation in the drying process can be suppressed, and a sufficient effect can be exerted in the calcining process. In addition, when the molecular weight per acetyl group is 120 or less, the decomposition-promoting effect of the binder can be further improved.

[0069] The boiling point of the acetated polyol is preferably 250° C. or higher.

[0070] By setting it as the said boiling point, when the slurry composition is applied and dried, it does not evaporate together with the organic solvent, and can exhibit the effect of accelerating the binder removal process.

[0071] The boiling point is preferably 400°C or lower, more preferably 270°C or higher, more preferably 370°C or lower, further preferably 300°C or higher, further preferably 350°C or lower. The boiling point is preferably 250-400°C, more preferably 270-370°C, further preferably 300-350°C.

[0072] The acetylated polyol having a boiling point of 270° C. or higher functions as a plasticizer. By using such an acetylated polyol, the amount of plasticizer added can be reduced.

[0073] It should be noted that the acetated polyol starts to burn at a temperature lower than 200°C in an air atmosphere, so the boiling point is preferably measured under reduced pressure. As a method for converting the boiling point under reduced pressure, the method of Science of Petroleum, Vol. II. p. 1281 (1938) can be used.

[0074] Examples of the polyol constituting the acetated polyol include glycerol, pentaerythritol, diethylene glycol, triethylene glycol, trimethylolpropane, maltitol, sorbitol, xylitol, erythritol, isomalt, etc. Among them, acetated products of glycerol, pentaerythritol, diethylene glycol, triethylene glycol, maltitol, sorbitol, xylitol, erythritol, and isomalt are preferred, because they can further promote the debinding process without increasing the oxygen partial pressure to significantly reduce the sintering residue, and further suppress the oxidation of inorganic particles to produce ceramic products with high reliability.

[0075] Specific examples of the acetated polyol include pentaerythritol tetraacetate (boiling point 325° C., oxygen atom content 42 wt %), triacetin (boiling point 258° C., oxygen atom content 44 wt %), triethylene glycol diacetate (boiling point 300° C., oxygen atom content 41 wt %), diethylene glycol diacetate (boiling point 250° C., oxygen atom content 42 wt %), ethylene glycol diacetate (boiling point 190° C., oxygen atom content 43.8 wt %), propylene glycol diacetate (boiling point 191° C., oxygen atom content 40 wt %), etc. Among them, pentaerythritol tetraacetate, triacetin, triethylene glycol diacetate, and diethylene glycol diacetate are preferred because they can further promote the binder removal process without increasing the oxygen partial pressure to significantly reduce the sintering residue, and further suppress the oxidation of inorganic particles to produce a ceramic product with high reliability.

[0076] The content of the acetated polyol in the slurry composition is 5 parts by weight or more and 40 parts by weight or less based on 100 parts by weight of the polyvinyl acetal resin.

[0077] By setting it as the said range, the binder removal process can be promoted and the residual carbon after firing can be reduced.

[0078] From the viewpoint of handling properties when forming a sheet, the content of the acetated polyol is preferably 10 parts by weight or more, preferably 30 parts by weight or less, more preferably 15 parts by weight or more, and more preferably 25 parts by weight or less, based on 100 parts by weight of the polyvinyl acetal resin. The content of the acetated polyol in the slurry composition is 5 to 40 parts by weight, preferably 10 to 30 parts by weight, and more preferably 15 to 25 parts by weight, based on 100 parts by weight of the polyvinyl acetal resin.

[0079] The content of the acetated polyol in the slurry composition is preferably 0.1% by weight or more, preferably 20% by weight or less, more preferably 0.2% by weight or more, more preferably 15% by weight or less, further preferably 0.4% by weight or more, further preferably 10% by weight or less. The content of the acetated polyol in the slurry composition is preferably 0.1 to 20% by weight, more preferably 0.2 to 15% by weight, further preferably 0.4 to 10% by weight.

[0080] By setting it as the said range, the binder removal effect can be fully improved, and the acetated polyol will not precipitate in a slurry composition, and it can make excellent printing property.

[0081] The slurry composition contains inorganic particles.

[0082] Examples of the inorganic particles include metal particles, glass powder, ceramic powder, phosphor particles, silicon oxide, and the like.

[0083] The metal particles are not particularly limited, and examples thereof include powders made of copper, nickel, palladium, platinum, gold, silver, aluminum, tungsten, and alloys thereof.

[0084] As the above-mentioned glass powder, for example, there can be mentioned: glass powders of bismuth oxide glass, silicate glass, lead glass, zinc glass, boron glass, etc.; glass powders of various silicon oxides such as CaO-Al2O3-SiO2 system, MgO-Al2O3-SiO2 system, LiO2-Al2O3-SiO2 system, etc.

[0085] In addition, as the above-mentioned glass powder, a SnO-B2O3-P2O5-Al2O3 mixture, a PbO-B2O3-SiO2 mixture, a BaO-ZnO-B2O3-SiO2 mixture, a ZnO-Bi2O3-B2O3-SiO2 mixture, a Bi2O3-B2O3-BaO-CuO mixture, a Bi2O3-ZnO-B2O3-Al2O3-SrO mixture, a ZnO-Bi2O3-B2O3 mixture, a Bi2O3-SiO2 mixture, a P2O5-Na2O-CaO-BaO-Al2O3-B2O3 mixture, a P2O5-SnO mixture, a P2O5-SnO-B2O3 mixture, or a P2O5-SnO-B2O3 mixture. Mixture, P2O5-SnO-SiO2 mixture, CuO-P2O5-RO mixture, SiO2-B2O3-ZnO-Na2O-Li2O-NaF-V2O5 mixture, P2O5-ZnO-SnO-R2O-RO mixture, B2O3-SiO2-ZnO mixture, B2O3-SiO2-Al2O3-ZrO2 mixture, SiO2-B2O3-ZnO-R2O-RO mixture, SiO2-B2O3-Al2O3-RO-R2O mixture, SrO-ZnO-P2O5 mixture, SrO-ZnO-P2O5 mixture, BaO-ZnO-B2O3-SiO2 mixture, etc. It should be noted that R represents an element selected from Zn, Ba, Ca, Mg, Sr, Sn, Ni, Fe and Mn.

[0086] Particularly preferred are lead-free glass powders such as glass powder of a PbO-B2O3-SiO2 mixture, a lead-free BaO-ZnO-B2O3-SiO2 mixture, or a ZnO-Bi2O3-B2O3-SiO2 mixture.

[0087] Examples of the ceramic powder include aluminum oxide, ferrite, zirconium oxide, zircon, barium zirconate, calcium zirconate, titanium oxide, barium titanate, strontium titanate, calcium titanate, magnesium titanate, zinc titanate, lanthanum titanate, neodymium titanate, lead zirconate titanate, aluminum nitride, silicon nitride, boron nitride, boron carbide, barium stannate, calcium stannate, magnesium silicate, mullite, steatite, cordierite, forsterite, and the like.

[0088] In addition, ITO, FTO, niobium oxide, vanadium oxide, tungsten oxide, lanthanum strontium manganate (Japanese: ランタンストロンチウムマンガナイト), lanthanum may also be used Strontium cobalt ferrite (Japanese: ランタンストロンチウムコバルトフェライト), yttrium-stabilized zirconia, gadolinium-doped ceria, nickel oxide, lanthanum chromate, etc.

[0089] By using the above-mentioned ceramic powder, it can be suitably used as a slurry composition for ceramic green sheets.

[0090] The inorganic particles contain lithium or titanium, so that they can be used as electrolyte slurry compositions for all-solid-state lithium-ion batteries. Specifically, for example, the inorganic particles containing lithium or titanium include low-melting-point glasses such as LiO2-Al2O3-SiO2 inorganic glasses, Li2S-M x S y (M=B, Si, Ge, P) and other lithium chalcogenide glasses, lithium cobalt composite oxides such as LiCoO2, lithium manganese composite oxides such as LiMnO4, lithium nickel composite oxides, lithium vanadium composite oxides, lithium zirconium composite oxides, lithium hafnium composite oxides, lithium silicon phosphate (Li 3.5 Si 0.5 P 0.5 O4), lithium titanium phosphate (LiTi2(PO4)3), lithium titanate (Li4Ti5O 12 ), Li4 / 3Ti5 / 3O4, lithium germanium phosphate (LiGe2(PO4)3), Li2-SiS glass, Li4GeS4-Li3PS4 glass, LiSiO3, LiMn2O4, Li2S-P2S5 glass·ceramics, Li2O-SiO2, Li2O-V2O5-SiO2, LiS-SiS2-Li4SiO4 glass, LiPON ion conductive oxides, Li2O-P2O5-B2O3, Li2O-GeO2Ba and other lithium oxide compounds, Li x Al y Ti z (PO4)3 series glass, La x Li y TiO z Glass, Li x Ge y P z O4 series glass, Li7La3Zr2O 12 Glass, Li v Si w P x S y Cl z Glass, lithium niobium oxides such as LiNbO3, lithium aluminum oxide compounds such as Li-β-alumina, Li 14 Lithium zinc oxides such as Zn(GeO4)4, etc.

[0091] The inorganic particles preferably have an average particle size of 200 nm or more and preferably 1 μm or less. The average particle size is preferably 0.2 to 1 μm.

[0092] By setting it as the said range, the characteristics of a laminated ceramic product can be improved. It should be noted that the average particle diameter of the said inorganic particle can be measured, for example, by the method of observation using a transmission electron microscope or the light scattering method of a dispersion liquid.

[0093] The content of the inorganic particles in the slurry composition is not particularly limited, but is preferably 10% by weight or more and preferably 90% by weight or less. The content of the inorganic particles in the slurry composition is preferably 10 to 90% by weight.

[0094] By setting it as the said range, sufficient viscosity can be given, excellent coating property can be obtained, and the dispersibility of an inorganic particle can be made excellent.

[0095] The slurry composition contains an organic solvent.

[0096] The organic solvent is not particularly limited, but is preferably an organic solvent that provides excellent coating properties, drying properties, dispersibility of inorganic particles, etc. when producing an inorganic particle-dispersed sheet.

[0097] Examples of the organic solvent include alcohols such as aliphatic alcohols, glycols, terpene alcohols, and aromatic alcohols, aromatic hydrocarbons, esters, ketones, and N-methylpyrrolidone.

[0098] Examples of the aliphatic alcohols include ethanol and isopropanol.

[0099] Examples of the diols include ethylene glycol monobutyl ether, diethylene glycol monoethyl ether, diethylene glycol monomethyl ether, diethylene glycol monoisobutyl ether, butyl carbitol, ethylene glycol monoethyl ether acetate, trimethylpentanediol monoisobutyrate, butyl carbitol acetate, Texanol, ethylene glycol monophenyl ether, propylene glycol monophenyl ether, and ethylene glycol ethyl ether.

[0100] Examples of the terpene alcohols include terpineol, dihydroterpineol, terpineol acetate, and dihydroterpineol acetate.

[0101] Examples of the aromatic alcohols include benzyl alcohol and the like.

[0102] Examples of the aromatic hydrocarbons include toluene and the like.

[0103] Examples of the esters include ethyl acetate, butyl acetate, hexyl acetate, isoamyl acetate, butyl butyrate, butyl lactate, dioctyl phthalate, and dioctyl adipate.

[0104] Examples of the ketones include methyl isobutyl ketone, methyl ethyl ketone, methyl isobutyl ketone, and isophorone.

[0105] Among them, alcohols and aromatic hydrocarbons are preferred, and dihydroterpineol acetate, ethanol, and toluene are more preferred.

[0106] It should be noted that these organic solvents may be used alone or in combination of two or more. In one embodiment of the present invention, the organic solvent is different from the acetated polyol.

[0107] The boiling point of the organic solvent is preferably 60°C or higher, preferably less than 260°C, more preferably 80°C or higher, and more preferably 240°C or lower. The boiling point is preferably 60°C or higher and less than 260°C, and preferably 80 to 240°C.

[0108] When the content is within the above range, the evaporation will not be too rapid, and the evaporation can be easily performed in a blower oven, etc. In addition, a ceramic green sheet having a smooth surface can be obtained.

[0109] The content of the organic solvent in the slurry composition is preferably 10% by weight or more, preferably 60% by weight or less, more preferably 20% by weight or more, more preferably 50% by weight or less. The content of the organic solvent in the slurry composition is preferably 10 to 60% by weight, more preferably 20 to 50% by weight.

[0110] By setting it as the said range, coating property and the dispersibility of an inorganic particle can be further improved.

[0111] The slurry composition may further include other additives such as a plasticizer, a surfactant, and a dispersant in addition to the polyvinyl acetal resin, the acetated polyol, the inorganic particles, and the organic solvent.

[0112] In the slurry composition, the acetylated polyol may be used as a plasticizer. However, when an acetylated polyol that is solid at room temperature is used or when the amount of the acetylated polyol added is small, it is preferred to add a plasticizer.

[0113] Examples of the plasticizer include di(butoxyethyl) adipate, dibutoxyethoxyethyl adipate, triethylene glycol dibutyl ether, triethylene glycol bis(2-ethylhexanoate), triethylene glycol dicaproate, acetylcitrate tributyl, and dibutyl sebacate.

[0114] It should be noted that the plasticizer is a substance different from the acetated polyol.

[0115] In addition, since a plasticizer having an aromatic ring such as a benzene ring in its structure easily burns to form ash, it is preferable to use a non-aromatic plasticizer, and it is preferable to use a plasticizer containing a component derived from adipic acid, triethylene glycol or citric acid.

[0116] The boiling point of the plasticizer is preferably 270° C. or higher, and preferably lower than 390° C. The boiling point is preferably 270° C. or higher and lower than 390° C.

[0117] When the content is within the above range, the carbon can be easily evaporated in the drying step, and can be prevented from remaining in the molded body, and can also be prevented from being generated as residual carbon.

[0118] It should be noted that the above-mentioned boiling point refers to the boiling point under normal pressure.

[0119] The content of the plasticizer in the slurry composition is not particularly limited, but is preferably 0.1% by weight or more and preferably 3.0% by weight or less. The content of the plasticizer in the slurry composition is preferably 0.1 to 3.0% by weight.

[0120] By setting it as the said range, both sheet handling property and sintering property can be achieved.

[0121] Examples of the surfactant include cationic surfactants, anionic surfactants, and nonionic surfactants.

[0122] As the above-mentioned nonionic surfactant, there is no particular limitation, and a nonionic surfactant having an HLB value of 10 or more and 20 or less is preferred. Here, the HLB value is a parameter used as an index of the hydrophilicity and lipophilicity of the surfactant. Several calculation methods have been proposed. For example, for ester-based surfactants, there are definitions such as setting the saponification value to S, setting the acid value of the fatty acid constituting the surfactant to A, and setting the HLB value to 20 (1-S / A). Specifically, a nonionic surfactant having polyethylene oxide formed by adding an alkylene ether to a fatty chain is suitable, and specifically, for example, polyoxyethylene lauryl ether, polyoxyethylene cetyl ether, etc. are suitable. It should be noted that the above-mentioned nonionic surfactant has good thermal decomposition, but if added in large quantities, the thermal decomposition of the inorganic particle dispersion slurry composition is sometimes reduced, so the preferred upper limit of the content is 5% by weight.

[0123] As the above-mentioned dispersant, for example, fatty acids, aliphatic amines, alkanolamides, and phosphoric acid esters are suitable. In addition, a silane coupling agent or the like may also be blended.

[0124] The fatty acid is not particularly limited, and examples thereof include saturated fatty acids such as behenic acid, stearic acid, palmitic acid, myristic acid, lauric acid, capric acid, caprylic acid, and coconut oil fatty acids; unsaturated fatty acids such as oleic acid, linoleic acid, linolenic acid, sorbic acid, tallow fatty acid, and hydrogenated castor oil fatty acid (Japanese: himasi hardened fatty acid), etc. Among them, lauric acid, stearic acid, oleic acid, etc. are suitable.

[0125] The aliphatic amine is not particularly limited, and examples thereof include laurylamine, myristicamine, cetylamine, stearylamine, oleylamine, alkyl(coconut)amine, alkyl(hydrogenated tallow)amine, alkyl(tallow)amine, and alkyl(soy)amine.

[0126] The alkanolamide is not particularly limited, and examples thereof include coconut oil fatty acid diethanolamide, tallow fatty acid diethanolamide, lauric acid diethanolamide, and oleic acid diethanolamide.

[0127] The phosphoric acid ester is not particularly limited, and examples thereof include polyoxyethylene alkyl ether phosphoric acid ester and polyoxyethylene alkyl allyl ether phosphoric acid ester.

[0128] The viscosity of the slurry composition is not particularly limited, but when measured at 20° C. using a B-type viscometer with a probe rotation speed set to 5 rpm, the preferred lower limit of the viscosity is 0.1 Pa·s and the preferred upper limit is 100 Pa·s. The viscosity is preferably 0.1 to 100 Pa·s.

[0129] By setting the viscosity to 0.1 Pa·s or more, the obtained inorganic particle dispersion sheet can maintain a predetermined shape after being coated by die coating printing method, etc. In addition, by setting the viscosity to 100 Pa·s or less, it is possible to prevent the undesirable situation such as the coating trace of the die not disappearing, thereby achieving excellent printability.

[0130] In the slurry composition preparation step, the method for mixing the polyvinyl acetal resin, the acetated polyol, the inorganic particles and the organic solvent is not particularly limited, and a conventionally known stirring method can be used. Specifically, for example, a method of mixing the polyvinyl acetal resin, the acetated polyol, the inorganic particles, the organic solvent, and other additives added as needed and stirring using a bead mill or the like can be used.

[0131] The resin composition preparation step preferably includes a coating and drying step of applying the slurry composition obtained in the slurry composition preparation step on a substrate and drying the slurry composition to prepare a resin composition.

[0132] The shape of the resin composition is not particularly limited. For example, the resin composition as an inorganic particle-dispersed sheet can be produced by applying the slurry composition onto a support film subjected to a one-side release treatment and drying the organic solvent to form a sheet.

[0133] The thickness of the inorganic particle dispersed sheet is preferably 0.5 to 20 μm.

[0134] As the substrate, a support film made of a resin having heat resistance and solvent resistance and flexibility can be used. By using a flexible support film, the inorganic particle dispersion slurry composition can be applied to the surface of the support film using a roll coater, a scraper coater, etc., and the resulting sheet-shaped resin composition can be stored and supplied in a state of being wound into a roll.

[0135] Examples of the resin forming the support film include polyethylene terephthalate, polyester, polyethylene, polypropylene, polystyrene, polyimide, polyvinyl alcohol resin, fluorine-containing resins such as polyvinyl chloride and polyvinyl fluoride, nylon, and cellulose.

[0136] The thickness of the support film is preferably, for example, 20 to 100 μm.

[0137] In addition, it is preferable to subject the surface of the support film to a release treatment, whereby the peeling operation of the support film can be easily performed in the transfer step.

[0138] Examples of a method for applying the slurry composition include a method using a roll coater, a knife coater, and the like.

[0139] Examples of the drying method include a blown oven and the like.

[0140] The content of the acetated polyol in the resin composition is 5 parts by weight or more and 40 parts by weight or less based on 100 parts by weight of the polyvinyl acetal resin.

[0141] By setting it as the said range, the binder removal process can be accelerated|stimulated and the residual carbon after firing can be reduced.

[0142] From the viewpoint of handling properties when forming a sheet, the content of the acetated polyol is preferably 10 parts by weight or more, preferably 30 parts by weight or less, more preferably 15 parts by weight or more, and more preferably 25 parts by weight or less, based on 100 parts by weight of the polyvinyl acetal resin. The content of the acetated polyol in the resin composition is 5 to 40 parts by weight, preferably 10 to 30 parts by weight, and more preferably 15 to 25 parts by weight, based on 100 parts by weight of the polyvinyl acetal resin.

[0143] In addition, the content of the acetated polyol in the resin composition is preferably 0.5% by weight or more, preferably 5% by weight or less, more preferably 0.75% by weight or more, more preferably 4.5% by weight or less. The content of the acetated polyol in the resin composition is preferably 0.5 to 5% by weight, more preferably 0.75 to 4.5% by weight.

[0144] The content of the polyvinyl acetal resin in the resin composition is preferably 4% by weight or more, preferably 15% by weight or less, more preferably 6.5% by weight or more, more preferably 11% by weight or less. The content of the polyvinyl acetal resin in the resin composition is preferably 4 to 15% by weight, more preferably 6.5 to 11% by weight.

[0145] The content of the inorganic particles in the resin composition is preferably 80% by weight or more, preferably 95% by weight or less, more preferably 85% by weight or more, more preferably 93% by weight or less. The content of the inorganic particles in the resin composition is preferably 80-95% by weight, more preferably 85-93% by weight.

[0146] The method for producing the inorganic sintered body comprises a sintering step of raising the temperature to the sintering temperature of the inorganic particles obtained in the resin composition preparation step to obtain the inorganic sintered body.

[0147] By performing the calcining step, an inorganic sintered body with less residual carbon can be produced. In addition, by using the inorganic sintered body as an electronic component, an electronic component with high reliability can be produced.

[0148] The conditions such as temperature and time in the calcining step are appropriately set according to the type of inorganic particles and are therefore not particularly limited. The temperature is preferably 900° C. or higher and preferably 1300° C. or lower. The temperature is preferably 900 to 1300° C. In addition, the time is preferably 1 hour or higher and preferably 6 hours or lower. The time is preferably 1 to 6 hours.

[0149] For example, when barium titanate is used, it is preferable to perform sintering under the conditions of 900° C. to 1200° C. and 20 minutes to 6 hours.

[0150] The heating rate is preferably 5°C / min or more, preferably 100°C / min or less, more preferably 20°C / min or more, more preferably 50°C / min or less. The heating rate is preferably 5 to 100°C / min, more preferably 20 to 50°C / min.

[0151] In addition, the sintering step is preferably carried out under an oxygen partial pressure of 10 -9 It is carried out in a reducing atmosphere containing H2-N2-H2O gas at a pressure of less than MPa.

[0152] In the above-mentioned method for producing an inorganic sintered body, by using the above-mentioned acetated polyol, the binder removal process can be easily performed even in an oxygen-poor environment, and residual carbon can be reduced. Therefore, the oxygen partial pressure in the reducing atmosphere can be reduced, and as a result, oxidation can be suppressed even when using a transition metal that is easily oxidized.

[0153] The oxygen partial pressure is preferably 10 -12 MPa or more, more preferably 10 -10 MPa or less. The above oxygen partial pressure is preferably 10 -12 ~10 - 9 MPa, more preferably 10 -12 ~10 -10 MPa.

[0154] The method for producing an inorganic sintered body preferably further comprises, before the calcining step, a binder removal step of maintaining the sintered body at 250° C. to 350° C. for 1 hour to 5 hours in a nitrogen atmosphere.

[0155] By providing the above-mentioned binder removal treatment step, the binder removal treatment can be promoted to reduce the organic components in the resin composition, thereby preventing the inorganic sintered body from being cracked due to the decomposition gas of the organic components in the subsequent calcining step.

[0156] The holding temperature in the binder removal treatment step is preferably 250° C. or higher and 350° C. or lower.

[0157] In order to reduce the residual carbon in the inorganic sintered body after sintering, the lower the temperature of the debindering treatment, the more preferably. Generally, the polyvinyl acetal resin will basically not decompose at a temperature below 300°C. In addition, at a temperature above 350°C, the carbonization of the polyvinyl acetal resin will proceed during the debindering treatment, and the residual carbon in the inorganic sintered body will increase. In the above-mentioned method for manufacturing the inorganic sintered body, the above-mentioned resin composition contains 5 parts by weight or more and 40 parts by weight or less of the above-mentioned acetated polyol relative to 100 parts by weight of the above-mentioned polyvinyl acetal resin, so that the debindering treatment can be carried out even at 250°C, and the residual carbon of the inorganic sintered body after sintering can be reduced. In addition, by carrying out the debindering treatment under the above-mentioned conditions, the binder component will not be completely removed, thereby preventing the rupture caused by the volume expansion of the inorganic particles and the decomposition gas.

[0158] The holding temperature is more preferably 270°C or higher, and more preferably 340°C or lower. The holding temperature is preferably 250 to 350°C, and more preferably 270 to 340°C.

[0159] The temperature increase rate from the binder removal holding temperature to the sintering temperature of the inorganic powder is preferably 20° C. / minute or more and 300° C. / minute or less. The temperature increase rate is preferably 20 to 300° C. / minute.

[0160] The retention time in the above-mentioned binder removal treatment step is preferably 1 hour to 5 hours.

[0161] By setting the above-mentioned holding time, the dehydration reaction of the polyvinyl acetal resin can be prevented from proceeding, and the binder component can be prevented from being difficult to decompose in the firing process. In addition, the inorganic sintered body can be prevented from being cracked in the firing process due to insufficient formation of gas exhaust holes in the inorganic sintered body.

[0162] The above-mentioned retention time is more preferably 2 hours or more, and more preferably 4 hours or less. The above-mentioned retention time is preferably 1 to 5 hours, and more preferably 2 to 4 hours.

[0163] As a method for producing the above-mentioned inorganic sintered body, the following method can be mentioned, for example.

[0164] First, a slurry composition preparation step is performed, that is, inorganic particles such as barium titanate and an organic solvent such as ethanol are mixed with a polyvinyl butyral resin as a binder resin, and an acetated polyol having a boiling point of 250° C. or higher and an oxygen atom content of 40% by weight or more is further mixed in an amount of 5 parts by weight or more and 40 parts by weight or less relative to 100 parts by weight of the polyvinyl butyral resin to prepare an inorganic particle-dispersed slurry composition.

[0165] Thereafter, a coating and drying step is performed in which the obtained inorganic particle dispersion slurry composition is coated on a release-treated PET film and dried to produce a raw inorganic particle dispersion sheet.

[0166] Furthermore, an electrode paste in which nickel powder is dispersed is printed on the inorganic particle dispersion sheet using a screen printer or the like. After drying, a plurality of sheets are stacked, heated and pressed, and punched to form an unprocessed laminate. Afterwards, the laminate is subjected to a debinding treatment process under a nitrogen atmosphere at a temperature of 250° C. or more and 350° C. or less for 1 hour or more and 5 hours or less. Next, a sintering process is performed, that is, the temperature is raised to 900° C. or more and 1200° C. or less, and sintered under the condition of 20 minutes or more and 6 hours or less. Thus, an inorganic sintered body can be obtained.

[0167] By the above-mentioned method for producing an inorganic sintered body, an inorganic sintered body as an electronic component can be produced.

[0168] It should be noted that, when manufacturing the above-mentioned electronic components, a part of the electronic components, such as only the internal electrodes or the dielectric layers, can be manufactured by the above-mentioned method for manufacturing inorganic sintered bodies, or multiple components of the electronic components, such as both the internal electrodes and the dielectric layers, can be manufactured by the above-mentioned method for manufacturing inorganic sintered bodies.

[0169] For example, in the above-mentioned structure, even when only the internal electrode is produced by the above-mentioned method for producing an inorganic sintered body, the degradation due to oxidation of the electrode layer can be suppressed, and a high-performance electronic component can be obtained. In addition, in the above-mentioned structure, even when only the dielectric layer is produced by the above-mentioned method for producing an inorganic sintered body, the generation of voids caused by the decomposition of the binder component in the dielectric layer can be suppressed, and a high-performance electronic component can be obtained. Furthermore, in the above-mentioned structure, when both the internal electrode and the dielectric layer are produced by the above-mentioned method for producing an inorganic sintered body, an electronic component with better performance can be obtained.

[0170] As the above-mentioned electronic components, for example, there can be mentioned: chip attach paste (ACP), chip attach film (ACF), TSV, TGV via electrodes, touch panels, various circuits of RFID or sensor substrates, various chip bonding agents, sealants for MEMS devices, solar cells, laminated ceramic capacitors, LTCC, silicon capacitors, electrode materials for all-solid-state batteries, etc. In addition, in addition to the above-mentioned electrode circuit uses, it can also be used for antibacterial components, electromagnetic wave shielding parts, catalysts, fluorescent materials, etc.

[0171] In addition, by using ceramic powder as inorganic particles, a ceramic sintered body can be produced.

[0172] The ceramic sintered body may be a ceramic laminate or a ceramic single layer body.

[0173] The above-mentioned ceramic laminates can be used for stacked ceramic capacitors, stacked ceramic substrates, all-solid-state batteries, etc., and the ceramic single layer can be used for ceramic packaging, low-temperature co-fired ceramics (LTCC), circuit substrates such as alumina, ceramic heat dissipation substrates such as aluminum nitride and silicon nitride, electrostatic chucks, ceramic columns, temperature sensors, piezoelectric elements, various mechanical parts, etc.

[0174] By using the above-mentioned inorganic sintered body as the material of the positive electrode, solid electrolyte, and negative electrode of the all-solid-state battery, an all-solid-state battery can be manufactured. In addition, conductive powders such as conductive metal particles can be used as inorganic particles to form electrode layers, and ceramic powders can be used as inorganic particles to form dielectric layers, and they can also be combined to manufacture stacked ceramic capacitors.

[0175] The conductive powder is not particularly limited as long as it is a material having conductivity, and examples thereof include nickel, palladium, indium, platinum, gold, silver, copper, and alloys thereof, etc. These conductive powders may be used alone or in combination of two or more.

[0176] In the above-mentioned method for producing an inorganic sintered body, when producing an inorganic sintered body as an electrode layer using conductive powder such as conductive metal particles, oxidation of the electrode layer can be suppressed even if easily oxidizable metal particles are used.

[0177] Furthermore, in the above-mentioned method for producing an inorganic sintered body, when the inorganic sintered body as a dielectric layer is produced using ceramic powder, the generation of voids due to the decomposition of the binder component can be suppressed.

[0178] The manufacturing method of the above-mentioned all-solid-state battery preferably includes: a step of using the above-mentioned slurry composition to prepare an inorganic particle dispersion sheet; a step of forming an electrode active material layer slurry containing an electrode active material and a binder for an electrode active material layer to prepare an electrode active material sheet; a step of stacking the above-mentioned electrode active material sheet and the above-mentioned inorganic particle dispersion sheet to prepare a stacked body; and a step of sintering the above-mentioned stacked body.

[0179] The method for producing a laminated ceramic capacitor preferably comprises: preparing an inorganic particle dispersion sheet using the slurry composition; printing a conductive paste on the inorganic particle dispersion sheet and drying the printed conductive paste to prepare a dielectric sheet; and laminating the dielectric sheets.

[0180] The above-mentioned conductive paste contains conductive powder.

[0181] The material of the conductive powder is not particularly limited as long as it has conductivity, and examples thereof include nickel, palladium, indium, platinum, gold, silver, copper, and alloys thereof. These conductive powders may be used alone or in combination of two or more.

[0182] The method for printing the conductive paste is not particularly limited, and examples thereof include screen printing, die coating printing, offset printing, gravure printing, and inkjet printing.

[0183] In the method for manufacturing the laminated ceramic capacitor, the laminated ceramic capacitor is obtained by laminating the dielectric sheet on which the conductive paste is printed and the electrode layer.

[0184] The unprocessed ceramic component on which the inorganic particle dispersion sheet containing the acetated polyol and the conductive paste composition are laminated is fired to produce a fired ceramic component, and external electrodes are further provided to produce an electronic component.

[0185] By providing external electrodes on the fired ceramic component, an electronic component can be manufactured.

[0186] The composition and setting method of the external electrode are not particularly limited. Metal plating, thermosetting conductive resin, metal paste, etc. can be preferably used. The metal that can be used for the metal paste is preferably a metal that has high conductivity and is sintered at a low temperature. For example, copper, nickel, silver, palladium, etc. can be mentioned.

[0187] Effects of the Invention

[0188] According to the present invention, it is possible to provide a method for producing an inorganic sintered body capable of reducing residual carbon after sintering and obtaining an electronic component with high reliability. DETAILED DESCRIPTION

[0189] Hereinafter, the present invention will be described in more detail with reference to Examples, but the present invention is not limited to these Examples.

[0190] (Preparation of Electrode Paste Composition A1)

[0191] 5 parts by weight of polyvinyl acetal resin (manufactured by Sekisui Chemical Co., Ltd., degree of polymerization 800, butyral group content 73 mol%, hydroxyl group content 22 mol%) as a binder resin, 1 part by weight of pentaerythritol tetraacetate as an acetated polyol, and 24 parts by weight of terpineol as an organic solvent were mixed in a sealed container and uniformly dissolved using a high-speed stirrer. 70 parts by weight of nickel powder (manufactured by JFE MINERAL Co., Ltd., NFP201) as inorganic particles were further added, and the nickel powder was dispersed using a three-roll mill to obtain a slurry composition (electrode paste composition A1).

[0192] (Preparation of Electrode Paste Composition B1)

[0193] Except having used the formulation of Table 1, a slurry composition (electrode paste composition B1) was obtained in the same manner as in “(Preparation of electrode paste composition A1)”.

[0194] (Preparation of Dielectric Slurry Composition A1)

[0195] 1.7 parts by weight of triacetin as an acetated polyol was added and dissolved in 20 parts by weight of an ethanol / toluene mixed solvent (weight ratio 1:1) as an organic solvent, and then 35 parts by weight of barium titanate (BT-02 manufactured by Sakai Chemical Industry Co., Ltd., average particle size 0.2 μm) was added as inorganic particles, and the inorganic particles were crushed using a bead mill. Further, a resin solution prepared by adding and dissolving 4.3 parts by weight of polyvinyl butyral resin (manufactured by Sekisui Chemical Co., Ltd., polymerization degree 1700, butyral group content 65 mol%) as a binder resin in 39 parts by weight of an ethanol / toluene mixed solvent (weight ratio 1:1) was added, and the mixture was stirred to crush the inorganic particles, thereby obtaining a slurry composition (dielectric slurry composition A1).

[0196] (Preparation of Dielectric Slurry Compositions A2 to A3, B1 to B4)

[0197] A slurry composition (dielectric slurry composition) was obtained in the same manner as in "(Preparation of dielectric slurry composition A1)" except that the acetated polyol and plasticizer shown in Table 1 were used and the formulation was set as Table 1. It should be noted that triethylene glycol-di-2-ethylhexanoate (3GO) was used as a plasticizer. In addition, the amount of the organic solvent in each solution was set to the same ratio as in "(Preparation of dielectric slurry composition A1)".

[0198] (Example 1)

[0199] (Manufacturing of Multilayer Ceramic Capacitors)

[0200] The obtained dielectric slurry composition A1 was applied onto a release-treated polyethylene terephthalate (PET) film using a die coater so that the film thickness after drying was 1 μm, and dried in a forced air oven at 120° C. for 30 minutes to prepare a ceramic green sheet.

[0201] The obtained ceramic green sheets are used to form an unprocessed laminate. Specifically, the obtained electrode paste composition A1 is screen-printed on the ceramic green sheets to form a conductive paste film that becomes an internal electrode. Next, a plurality of ceramic green sheets formed with the conductive paste film are stacked so that the lead-out sides of the conductive paste film are different from each other, and then pressure-bonded to obtain an unprocessed laminate.

[0202] Next, the unprocessed laminate was sintered. Specifically, first, it was heated at 250°C for 5 hours in a nitrogen atmosphere to remove the binder. Then, it was sintered at an oxygen partial pressure of 10 -12 The temperature was raised to 1200°C at a rate of 20°C / min in a reducing atmosphere containing H2-N2-H2O gas at MPa, and sintered at 1200°C for 3 hours to obtain a laminated sintered body. This was copper plated to obtain a laminated ceramic capacitor.

[0203] (Examples 2 to 3, Comparative Examples 1 to 4)

[0204] A multilayer ceramic capacitor was obtained in the same manner as in Example 1 except that the combinations of the electrode paste composition and the dielectric slurry composition were as shown in Table 2 and the oxygen partial pressure during the binder removal treatment and the firing treatment was changed as shown in Table 2.

[0205] (evaluate)

[0206] The obtained laminated sintered body and laminated ceramic capacitor were evaluated as follows.

[0207] (1) Residual carbon

[0208] The obtained stacked sintered body was pulverized, and the residual carbon content was measured based on the CO and CO2 amounts obtained by high-frequency induction heating furnace combustion-infrared absorption method. A residual carbon content of 200 ppm or less was evaluated as "0", and a residual carbon content exceeding 200 ppm was evaluated as "×".

[0209] (2) Oxidation degree of electrode layer

[0210] The cross section of the internal electrode layer of the obtained multilayer ceramic capacitor was evaluated using a Raman microscope NR-3100 manufactured by Jasco Corporation at 500 cm -1 The presence or absence of oxidation of the nickel powder was evaluated as follows based on the Raman shift of the nearby nickel oxide.

[0211] Unoxidized: The top of the scattering peak is 530 cm -1 surrounding.

[0212] Oxidized: The top of the scattering peak shifts to 550cm -1 Above the high wave number side.

[0213] (3) Gaps in the dielectric layer

[0214] The cross section of the dielectric layer of the obtained multilayer ceramic capacitor was observed using SEM and evaluated according to the following criteria: It is considered that the voids in the dielectric layer are caused by decomposition gas of the resin.

[0215] A: No gap has been confirmed.

[0216] B: One or more and less than five gaps were confirmed.

[0217] C: 5 or more and less than 10 gaps were confirmed.

[0218] D: Ten or more gaps were confirmed.

[0219] (4) Equivalent series resistance

[0220] Ten of the obtained laminated ceramic capacitors were heat treated at 150°C for 1 hour in an air atmosphere, and then mounted on a measurement substrate. After 24±2 hours after the heat treatment, the equivalent series resistance (ESR) was measured using a network analyzer. The measurement frequency was set to 10 MHz. The values ​​of each of the ten were averaged, and the case of less than 48 mΩ was evaluated as "0", and the case of more than 48 mΩ was evaluated as "×".

[0221] [Table 1]

[0222]

[0223]

[0224] Industrial Applicability

[0225] According to the present invention, it is possible to provide a method for producing an inorganic sintered body capable of reducing residual carbon after sintering and obtaining an electronic component with high reliability.

Claims

1. A method for producing an inorganic sintered body, comprising: A resin composition preparation step of preparing a resin composition containing a polyvinyl acetal resin, an acetated polyol and inorganic particles; and a sintering step of heating the resin composition to a sintering temperature of the inorganic particles to obtain an inorganic sintered body. The oxygen atom content of the acetated polyol is 40% by weight or more, The content of the acetated polyol in the resin composition is 5 parts by weight or more and 40 parts by weight or less based on 100 parts by weight of the polyvinyl acetal resin.

2. The method for producing an inorganic sintered body according to claim 1, wherein: The acetylated polyol is an acetylated product of at least one polyol selected from the group consisting of glycerol, pentaerythritol, diethylene glycol, and triethylene glycol. 3 . The method for producing an inorganic sintered body according to claim 1 , further comprising, before the sintering step, a binder removal step of maintaining the mixture at a temperature of 250° C. to 350° C. in a nitrogen atmosphere for 1 hour to 5 hours.

4. The method for producing an inorganic sintered body according to claim 3, wherein: The sintering process is carried out at an oxygen partial pressure of 10 - 10 It is carried out in a reducing atmosphere containing H2-N2-H2O gas at a pressure of less than MPa.

Citation Information

Patent Citations

  • Solvent-containing composition for manufacturing laminated ceramic component

    CN101989494A

  • Production of laminated ceramic electronic part

    JP1996073273A

  • Paste for laminated ceramic electronic component

    JP2011148649A

  • Slurry composition for dispersing inorganic fine particle, inorganic fine particle dispersion sheet, and manufacturing method of inorganic fine particle dispersion sheet

    JP2021042370A